Journalistic discourse of intercultural communications [Book review: Professional culture of journalist: Problems of intercultural communication: Interuniversity collection of papers] - L.G. Egorova; D.V. Tumanov (Ученые записки Казанского университета: Серия Гуманитарные науки)
-